Malignant melanoma of glans penis and prepuce treated with organ-preserving surgical procedure - Slavov, Chavdar (Array, 2009)
Summary: The authors present a case of malignant melanoma of glans penis and prepuce. An organ-preserving operative procedure using buccal mucosa was performed with subsequent inguino-femoral modified lymphadenectomy. There was no disease progression during the follow-up period of twelve months